Enhancing Digital Literacy and Religious Moderation through an E-Book on Madrasah Principal Leadership in Islamic Boarding School Culture - Khoiri, Nur; Hidayat, Saifullah; Mashudi, Mashudi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to assess the effectiveness of e-book development as a concrete effort to support the vision of intellectually and spiritually superior madrasah education. The method used was a quasi-experimental design with data collection techniques including interviews, observations, and questionnaires. Qualitative data were analysed descriptively, while quantitative data were analysed using paired t-tests on pretest and posttest results. The findings show that the e-book on madrasah principal leadership grounded in Islamic boarding school culture is efficacious in improving students' digital literacy. This is indicated by the t-test result (0.014 < 0.05), which shows a significant difference between pretest and posttest scores, and by an N-gain score of 2.795 (279.52%), which falls into the high and highly effective category. The e-book was found to be less effective in improving students' religious moderation. Although the t-test result (0.000 < 0.05) indicates a significant difference, the N-gain score was only 0.482 (48.2%), which is considered moderate and interpreted as less effective according to the effectiveness Table. Therefore, while the e-book has proven more effective at enhancing students' digital literacy, it still requires further development to instil values of religious moderation effectively.